Development and Evaluation of Lessoncast in Learning Selected Basic Technology Concept in Ilorin Metropolis - Aladesusi Gboyega Ayodeji; Adegbokan Oluwatosin NIfemi; Onasanya Samuel A.; Onasanya Temitayo Omolara (Indonesian Journal of Educational Research and Technology, 2022)
This study determined the development and evaluation of Lessoncast in learning selected Basic Technology concept in Ilorin Metropolis. The study adopted a design and development model type. The population for this study was 5 educational technology experts, 5 computer science experts and 5 basic technology teachers were randomly selected to participate in the study. Two research instrument were used in this study; a developed lessoncast on basic technology; an experts rating questionnaire for the selected experts. Percentage and mean were used to answer the research questions. The findings indicated that Lessoncast in upper basic technology can be successfully developed for teaching upper basic technology. Educational technology experts agreed that developed lesson cast satisfied the required expectation. This study concluded that the visual aids or materials such as lesson cast work as a powerful tool in the classroom and can be used to enhance the teaching of basic technology in Nigeria. The implication is that if Lessoncast is properly integrated into teaching and learning, it will concretize the teaching and learning of basic technology concept. Therefore, the study recommended that schools should make resources such as the Internet and computers available to basic technology teachers so as to design and develop appropriate classroom learning and teaching materials that would help to explain concepts in basic technology better.